Legal Implications of ESG Integration on Talent Management Policies in Indonesia's Renewable Energy Sector: An Analysis of Regulations and Corporate Practices - Syaiful Ali; Hery Chariansyah; Heryawan Heryawan (jurnal.unprimdn.ac.id, 2026)
The energy transition in Indonesia demands corporate governance restructuring through the integration of Environmental, Social, and Governance (ESG) criteria, which is currently transforming from voluntary disclosure to mandatory compliance. This article analyzes how energy regulations in Indonesia, particularly regarding the Domestic Component Level (TKDN) and sustainability reporting, directly impacts the reconstruction of talent management policies. The novelty of this research lies in filling the interdisciplinary research gap that bridges upstream economic law with downstream corporate labor law. Utilizing a normative-juridical research method and an empirical approach, the study finds that sectoral regulatory fragmentation and extreme skills gaps serve as the primary obstacle in fulfilling corporate legal compliance. The results of multiple linear regression analysis and Structural Equation Modeling-Partial Least Squares (SEM-PLS) demonstrate a coefficient of determination (R^2) value of 0.635, confirming that 63.5% of the variance in human resource sustainability is significantly influenced by the integration of Green Human Resource Management (Green HRM) and talent management. Compliance with energy regulations compels corporations to adopt Green HRM to mitigate legal risks and fulfill the 2060 Net Zero Emission (NZE) ambition. Legal engineering through the harmonization of the RPOJK draft adoption of IFRS S2, alongside the digitization of HR master data, is an absolute prerequisite for mitigating employment greenwashing risks and maintaining corporate legal compliance.